2022
DOI: 10.47405/mjssh.v7i6.1568
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Employees on Work-From-Home During Movement Control Order in Malaysia

Abstract: The COVID-19 pandemic has made Work from Home (WFH), an officially mandated and strictly enforced rule. The WFH concept is already gaining traction across many industries mainly requires in non-essential companies. Most employees are not satisfied with the WFH concept, as COVID-19 has required practically some employees from non-essential industries to work from home for the first time. This paper aims to discuss employees' perception of work from home during the movement control order in Malaysia as employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The present study's identification of a negative association between COVID-19 containment measures and employee satisfaction in SMEs is consistent with prior research, as exemplified by the studies conducted by Bakar et al (2022) and Bajrami et al (2021). These studies also observed a similar trend, indicating that employees experienced dissatisfaction with remote work during the COVID-19 period.…”
Section: Discussionsupporting
confidence: 90%
“…The present study's identification of a negative association between COVID-19 containment measures and employee satisfaction in SMEs is consistent with prior research, as exemplified by the studies conducted by Bakar et al (2022) and Bajrami et al (2021). These studies also observed a similar trend, indicating that employees experienced dissatisfaction with remote work during the COVID-19 period.…”
Section: Discussionsupporting
confidence: 90%
“…In the public sector, with the continuous rising of Covid-19 active cases from March 2020 to 25 March 2021, civil servants are permitted to WFH. As the country moved forward into the endemic stage with the National Recovery Plan, almost 80% of civil servants WFH are permitted to work at their premises (Abu Bakar et al, 2022). On the contrary, the private sector in Malaysia implements the practice on a different basis due to the need to avoid an economic shutdown (Tambou et al, 2021).…”
Section: Background Of Studymentioning
confidence: 99%